New Report on the Symbiotic Relation of Ochotona roylei (Lagomorpha: Ochotonidae) and Scaly Breasted Wren Babbler (Pnoepyge albiventer) at Ganesh Himalaya Area of Central Nepal - Khanal, Bhaiya (Our Nature, 2008)
The symbiotic relationship of bird and pika is still a least understood phenomenon in biological science. This study at 3300 m near Somdang of Ganesh Himal area of central Nepal provided a new and interesting information on the behavior of Royle’s Pika (Ochotona roylei) which shared its haypile with a bird called Scaly Breasted Wren Babbler (Pnoepyge albiventer). Among the inspected 11 haypiles one haypile was observed sheltering both bird and pika. Keywords: Symbiotic, behavior, haypiles, pika, relationship doi:10.3126/on.v5i1.796 Our Nature (2007)5:37-40